2020
DOI: 10.3390/rs12010115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Multispectral Sensors for Photosynthetic and Non-Photosynthetic Vegetation-Fraction Retrieval

Abstract: It is very difficult and complex to acquire photosynthetic vegetation (PV) and non-PV (NPV) fractions (fPV and fNPV) using multispectral satellite sensors because estimations of fPV and fNPV are influenced by many factors, such as background-noise interference of pixel-, spatial-, and spectral-scale effects. In this study, comparisons between Sentinel-2A Multispectral Instrument (S2 MSI), Landsat-8 Operational Land Imager (L8 OLI), and GF1 Wide Field View (GF1 WFV) sensors for retrieving sparse photosynthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Our results confirm previous studies showing that multispectral data, and in particular Sentinel-2, are well suited for mapping the PV fraction accurately (e.g. Corbane et al, 2014;Guerschman et al, 2015;Ji et al, 2020). Using PV fractional cover reduces saturation effects (Gitelson et al, 2002) as well as sensitivity deficiencies under drought (Xu et al, 2014).…”
Section: Pv Npv and Soil Fractional Cover Time Series From Sentinel-2supporting
confidence: 89%
See 1 more Smart Citation
“…Our results confirm previous studies showing that multispectral data, and in particular Sentinel-2, are well suited for mapping the PV fraction accurately (e.g. Corbane et al, 2014;Guerschman et al, 2015;Ji et al, 2020). Using PV fractional cover reduces saturation effects (Gitelson et al, 2002) as well as sensitivity deficiencies under drought (Xu et al, 2014).…”
Section: Pv Npv and Soil Fractional Cover Time Series From Sentinel-2supporting
confidence: 89%
“…However, similar to Guerschman et al (2009), we found that NPV typically has a considerably lower reflectance than soil in the SWIR band centered on 2200 nm, increasing the spectral separability of NPV and soil for our study area. Second, results by Ji et al (2020) and Tian et al (2021) suggest, that the three red-edge bands and the relatively narrow NIR band of Sentinel-2 provide additional information for separating NPV from soil. NPV often exhibits a stronger reflectance increase in the red-edge wavelength region towards the NIR than soils.…”
Section: Pv Npv and Soil Fractional Cover Time Series From Sentinel-2mentioning
confidence: 99%
“…PlanetScope and Sentinel-2 were both found to be spatially and temporally suitable to capture the trajectory of almond flower blooming and its critical stages through the use of EBI. Although it is not surprising that the very high-resolution ceres dataset provides the maximum capacity in detecting blooming signals early in the season, it would be interesting to see if the flowers and other parts of the vegetation can be unmixed from coarser resolution data as mentioned in Ji et al (2020) [75], who reported the capability of the visible bands and red-edge bands in discriminating the photosynthetic and non-photosynthetic fractions. Several studies have used spectral mixture analyses to identify photosynthetic and non-photosynthetic fractions [76][77][78] and vegetation indices to estimate concentration of plant pigments [79][80][81].…”
Section: Vegetation Indices For Phenological Research In Woody Speciesmentioning
confidence: 99%
“…Forest management explicitly necessitates the use of remotely sensed data owing to its cost effectiveness and regional availability. These data has been investigated in terms of data accuracy and reliability in many applications including those of vegetation, agriculture, and forestry [8][9][10]. Therefore, research focus is being increasingly centred on mapping the quantitative distribution of forest stand characteristics (e.g., diameter, height, location, basal area, potential volume of wood, and tree species) as a forest management strategy [1,6].…”
Section: Introductionmentioning
confidence: 99%